2010
DOI: 10.1007/s10548-010-0134-1
|View full text |Cite
|
Sign up to set email alerts
|

Regional Differences in the Sensitivity of MEG for Interictal Spikes in Epilepsy

Abstract: MEG interictal spikes as recorded in epilepsy patients are a reflection of intracranial interictal activity. This study investigates the relationship between the estimated sources of MEG spikes and the location, distribution and size of interictal spikes in the invasive ECoG of a group of 38 epilepsy patients that are monitored for pre-surgical evaluation. An amplitude/surface area measure is defined to quantify and rank ECoG spikes. It is found that all MEG spikes are associated with an ECoG spike that is amo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
0
3

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(43 citation statements)
references
References 10 publications
1
37
0
3
Order By: Relevance
“…Magnetoencephalography shows good agreement with subsequently performed ECoG [30][31][32][33][34][35][36]. These studies indicate that all spikes have an ECoG correlate, and about 2/3rd of all ECoG spikes are detected by MEG [37]. Studies validating MEG using subsequent ECoG should be interpreted with care since epileptic discharges can vary in time and space within the irritative/epileptogenic zone [15].…”
Section: Meg Localization Compared With Electrocorticography (Ecog)mentioning
confidence: 59%
See 1 more Smart Citation
“…Magnetoencephalography shows good agreement with subsequently performed ECoG [30][31][32][33][34][35][36]. These studies indicate that all spikes have an ECoG correlate, and about 2/3rd of all ECoG spikes are detected by MEG [37]. Studies validating MEG using subsequent ECoG should be interpreted with care since epileptic discharges can vary in time and space within the irritative/epileptogenic zone [15].…”
Section: Meg Localization Compared With Electrocorticography (Ecog)mentioning
confidence: 59%
“…Insular onset suspected Interhemispheric (especially frontal) onset suspected MEG can detect spikes from the interhemispheric area [10,37,50]. MEG can lateralize medial frontal spikes even when the EEG is nonlateralizing because of varying dipole orientation or secondary bisynchrony [50].…”
Section: Clinical Scenario Commentsmentioning
confidence: 99%
“…As mentioned by Huiskamp et al [11], inter-ictal spikes are spontaneous signals that can have relatively large amplitude (∼3 pT in MEG). This implies that epileptic MEG signals are likely to arise from large spatially extended regions of active cortex [12].…”
Section: Introductionmentioning
confidence: 96%
“…A study by Mikuni et al [13] suggested that MEG can detect epileptiform activity when a cortical area greater than 4 cm 2 is synchronously involved. Comparing MEG spikes with Electro-CorticoGraphy (ECoG) spikes, studies performed by Oishi et al [14] and Huiskamp et al [11] showed that MEG sensitivity varies for different regions in the brain. As a result, not only the size of the generators matters, but their location and orientation affect the detection of the MEG epileptic activity [1], [13].…”
Section: Introductionmentioning
confidence: 99%
“…Im MEG ist das Signal-zu-Rausch-Verhältnis für Quellen im Frontallappen besser als im EEG, sodass es hier eine besonders hohe Sensitivität hat [15,23]. Ossenblok et al [46] untersuchten Patienten mit Frontallappenepilepsien mithilfe der MEG-und EEG-Quellenanalyse.…”
Section: Frontallappenepilepsieunclassified